Studi tentang "negara Pancasila sebagai darul ahdi wa syahadah" untuk penguatan materi pembelajaran Pendidikan Kewarganegaraan di Universitas Ahmad Dahlan - Arif, Dikdik Baehaqi; Aulia, Syifa Siti (Jurnal Civics: Media Kajian Kewarganegaraan, 2017)
This research-based article tries to dig the conception of Pancasila-based State as Darul Ahdi Wa Syahadah to enlarge and enrich teaching materials of Citizenship Education for students at Muhammadiyah Higher Education. It is argued that this effort is to give them basic comprehension of conceptual as well as practical dimensions of the relation among state, Pancasila, and Islam in accordance with Muhammadiyah doctrine. Unit of analysis is the coordinators of Citizenship Education at Ahmad Dahlan University. Data was collected through interview and document reading. Interviewees were coordinators and lecturers of the program chosen purposively. It is argued that the urgency of conception of Pancasila-based State as Darul Ahdi Wa Syahadah to strengthen and enlarge teaching materials of Citizenship Education at Ahmad Dahlan University due to its accordance with its vision and mission as an institution under Muhammadiyah Higher Education Foundation.